Individual Proton Pump Inhibitors and Outcomes in Patients With Coronary Artery Disease on Dual Antiplatelet Therapy: A Systematic Review. Issue 11 (November 2015) - Sherwood, Matthew W.; Melloni, Chiara; Jones, W. Schuyler; Washam, Jeffrey B.; Hasselblad, Vic; Dolor, Rowena J.
Abstract : Background: Observational studies evaluating the possible interaction between proton pump inhibitors (PPIs) and clopidogrel have shown mixed results. We conducted a systematic review comparing the safety of individual PPIs in patients with coronary artery disease taking clopidogrel. Methods and Results: Studies performed from January 1995 to December 2013 were screened for inclusion. Data were extracted, and study quality was graded for 34 potential studies. For those studies in which follow‐up period, outcomes, and multivariable adjustment were comparable, meta‐analysis was performed. The adjusted odds or hazard ratios for the composite of cardiovascular or all‐cause death, myocardial infarction, and stroke at 1 year were reported in 6 observational studies with data on individual PPIs. Random‐effects meta‐analyses of the 6 studies revealed an increased risk for adverse cardiovascular events for those taking pantoprazole (hazard ratio 1.38; 95% CI 1.12–1.70), lansoprazole (hazard ratio 1.29; 95% CI 1.09–1.52), or esomeprazole (hazard ratio 1.27; 95% CI 1.02–1.58) compared with patients on no PPI. This association was not significant for omeprazole (hazard ratio 1.16; 95% CI 0.93–1.44). Sensitivity analyses for the coronary artery disease population (acute coronary syndrome versus mixed) and exclusion of a single study due to heterogeneity of reported results did not have significant influence on the effect estimates for any PPIs. Conclusions: Several frequently used PPIs previously thought to be safe for concomitant use with clopidogrel were associated with greater risk of adverse cardiovascular events. Although the data are observational, they highlight the need for randomized controlled trials to evaluate the safety of concomitant PPI and clopidogrel use in patients with coronary artery disease.